Behavior of the PMD coefficient of optical links under influence of mechanical and thermal effects - Dotto, Jeancarlo; Medeiros Neto, Januncio A. de [UNESP]; Pohl, Alexandre A. P. (My University, 2004)
This papers presents results on the variation of the PMD coefficient of optical links under influence of mechanical tests, such as tensile strength, bending and compression, and also during the application of a thermal cycle. Results revealed that the link coefficient is more influenced by the application of a tension load and also suffers significant variation under strong temperature changes. Copyrigth © SBMO.
Keywords: Environment Effects on Cables; Optical Cables; PMD Link Coefficient; Polarization Mode Dispersion; Environment effects; Mechanical and thermal effects; Mechanical tests; Temperature changes; Tension loads; Thermal cycle; Bending strength; Bending tests; Optical cables; Polarization mode dispersion; Optical links